1994
DOI: 10.1016/0550-3213(94)90428-6
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic genera and N = 2 superconformal field theory

Abstract: Recently Witten proposed to consider elliptic genus in N = 2 superconformal field theory to understand the relation between N = 2 minimal models and Landau-Ginzburg theories. In this paper we first discuss the basic properties satisfied by elliptic genera in N = 2 theories. These properties are confirmed by some fundamental class of examples.Then we introduce a generic procedure to compute the elliptic genera of a particular class of orbifold theories, i.e. the ones orbifoldized by e 2πiJ 0 in the Neveu-Schwar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
290
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(294 citation statements)
references
References 39 publications
4
290
0
Order By: Relevance
“…Our discussion here parallels that in [9]; also useful are [12,13]. The focus will be on theories with either (4, 4) or (0, 4) supersymmetry, though in fact replacing any of the 4's by 2's makes almost no difference.…”
Section: Review: Partition Functions In Cftmentioning
confidence: 88%
“…Our discussion here parallels that in [9]; also useful are [12,13]. The focus will be on theories with either (4, 4) or (0, 4) supersymmetry, though in fact replacing any of the 4's by 2's makes almost no difference.…”
Section: Review: Partition Functions In Cftmentioning
confidence: 88%
“…The elliptic genus of a CY d-fold, Z CY d (τ, z) with τ, z ∈ C and Im(τ ) > 0, is a weight 0 and index d/2 weak Jacobi form [23]. A Jacobi form φ k,m (τ, z) of weight k and index m satisfies…”
Section: Jacobi Formsmentioning
confidence: 99%
“…The K3 surface is the lowest dimensional non-trivial compact Calabi-Yau manifold. Its geometric symmetries at different points in moduli space have been classified by Mukai and Kondo [11,12] who found that the symplectic automorphisms of any K3 manifold form a subgroup of the Mathieu group M 23 . This means that no particular K3 surface has M 24 as symmetry group.…”
Section: Jhep02(2018)129mentioning
confidence: 99%
See 2 more Smart Citations